Synthesis of a far-red fluorophore and its use as an esterase probe in living cells. Issue 9 (15th December 2015) - Levine, Samantha R.; Beatty, Kimberly E.
Abstract : A new esterase-activatable probe expands the toolkit for staining living cells with a far-red fluorescent carbazine. Abstract : We report the synthesis of a new far-red fluorophore, 1, 3-dichloro-7-hydroxy-2 H -spiro[acridine-9, 1′-cyclohexane]-2′, 5′-diene-2, 4′-dione (DSACO), which was modified to make two esterase probes: DSACO-2-AME and DSACO-7-AME. Both probes act as "turn-on" substrates for esterases and lipases. DSACO-2-AME exhibited efficient esterase-activated fluorescence inside living cells and is a stable, far-red alternative for the widely-used fluorescein diacetate.